Medicinais plants in anti-aging: an integrative review (Research, Society and Development, 2023)
Aging occurs due to a cellular functional decline related to intrinsic and extrinsic factors, causing changes in genetic material, an increase in reactive oxygen species, destruction of elastic fibers and collagen, resulting in the characteristic phenotype of aging in terms of dermatology. Therefore, phytotherapy consists of using plants for medicinal purposes, which are studied and used to attenuate the effects of aging, reducing this phenotype and molecular alterations. Thus, the present study aimed to investigate scientific literature regarding the relationship between medicinal plants and aging. The descriptors "Skin Aging," "Medicinal Plants," and "Phytotherapy" were used in the Virtual Health Library, using MEDLINE and LILACS. Twelve articles composed the final sample and brought beneficial results about the use of medicinal plants during the aging process. Through in vitro and in vivo studies, it was demonstrated that certain plants can improve skin appearance, reduce oxidative stress, improve the disposition of matrix proteins, among others. Finally, it is concluded that the application of medicinal plants Acan be an important tool in combating oxidative stress, reducing DNA damage, and biochemical reactions that lead to accelerated skin aging.